Des enseignants d’histoire face à une question socialement vive : ressources et supports de travail en classe. Les traites négrières en cinquième et quatrième - Pierre Carion (Recherches en Éducation)
The connections beetwen history and memory, reinforced by the demand of duty of memory, explain that French scholar history and school history are permeated by social and political debates. Slave trades, a prescribed thematics in school, might thus be defined as a « Question Socialement Vive » (social acute question, or sensitive issue). In this context, studying the documentary resources mobilized by the teachers who teach slave trades in the second and third years of secondary school provides an opportunity to question their professorial practices. This article, based on the 1st year of a doctoral research, associates an exploratory enquiry amon teachers with an analyse of the textbooks from the second year of secondary school, and stress the obstacles to take in charge such QSV.